Analisis Pengaruh Lingkungan Belajar Terhadap Pengembangan Literasi Numerasi Siswa Sekolah Dasar - Alfi Rahmawati; Ermita Asih; Nayla Husniyah; Shania Ratih A; Tia Citra Bayuni (Arfah BHMS Foundation, 2026)
This study aims to analyze the influence of the learning environment on the development of numeracy literacy among elementary school students. Using a descriptif quantitative approach with a survey method based on a Likert scale, data were collected from students and teachers in several elementary schools. Descriptive statistics and regression analysis were employed to identify the most influential learning environment factors on numeracy literacy. Results indicate that learning environment factors, such as classroom atmosphere, facilities, and teaching methods, significantly impact students' numeracy skills. These findings emphasize the importance of a conducive learning environment in supporting basic numeracy development. The application of this research is expected to improve learning environments and enhance numeracy literacy at the elementary level.